Identification of stakeholders and conflicts of interest in the Ecuador Savings and credit cooperatives - Altamirano Salazar, Aníbal (2018)
Fil: Altamirano Salazar, Aníbal. University of the Armed Forces ESPE. Administrative Sciences; Ecuador.